2001
DOI: 10.1089/08927790152596271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Laparoscopic Retroperitoneal Surgery in Urinary Stone Disease

Abstract: Laparoscopic retroperitoneal surgery has a definite role in the management of patients requiring open surgery for calculous disease. It is safe and feasible in spite of the dense adhesions that are frequently encountered in such patients. Often, previous attempts at treatment with shockwave lithotripsy or endourologic procedures also lead to inflammation and adhesions, making surgery difficult. However, these problems can be dealt with by LRS with good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 20 publications
2
31
0
2
Order By: Relevance
“…Our results were corroborated by the findings of the study conducted by Sinha et al [3] , which reported an average hospital stay of 3.6 days for patients who underwent laparoscopic pyelolithotomy. Similar results were reported by Goel et al [6] in their study, in which the hospital stay for laparoscopic pyelolithotomy patients was 3-4 days. Soares et al [11] reported that, in their study, the average hospital stay was 3 days (range 1-10) for laparoscopic pyelolithotomy patients.…”
Section: Hospital Staysupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were corroborated by the findings of the study conducted by Sinha et al [3] , which reported an average hospital stay of 3.6 days for patients who underwent laparoscopic pyelolithotomy. Similar results were reported by Goel et al [6] in their study, in which the hospital stay for laparoscopic pyelolithotomy patients was 3-4 days. Soares et al [11] reported that, in their study, the average hospital stay was 3 days (range 1-10) for laparoscopic pyelolithotomy patients.…”
Section: Hospital Staysupporting
confidence: 91%
“…Alaa el-ghomeni et al [5] reported an operative time of 135 min for laparoscopic pyelolithotomy. Hemal, Kumar et al [6] reported an operative time of 108.2 min. for laparoscopic pyelolithotomy.…”
Section: Operative Timementioning
confidence: 99%
See 1 more Smart Citation
“…Hamal et al [25] reported a success rate of 75% in their LRU series and explained that open conversion occurred early in their work and was related to the stepwise learning curve. Also, Jeong et al [26] reported a high rate of change to open surgery (50%) as they opened 6 of 12 patients due the failure of ureter identification because of adhesion and periureteritis in 5 patients and vascular injury in 1.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, successful laparoscopic management of renal stones has been described; however, the indications have not yet been defined and outcomes have not been compared with established techniques, such as PNL. 17,18 In the current study, LPL was evaluated as a surgical monotherapy to manage renal pelvic stones and compared with PNL. In our study, the preoperative data of both groups were homogenous with no statistically significant difference regarding age, sex and stone size.…”
Section: Discussionmentioning
confidence: 99%